'Resilience without development' in a remote rural West African community: the case of Kayima, Sierra Leone. Issue 3 (September 2022) - Binns, Tony; Bateman, Jerram
Abstract: Relatively few longitudinal studies have been undertaken of change and development among rural communities in Africa. Drawing on field-based research conducted over almost five decades, the article examines the shocks and adaptive strategies experienced in the remote rural community of Kayima in north-eastern Sierra Leone. In coping with both external and internal shocks and displaying a remarkable level of resilience, there has however been very little improvement in community livelihoods, and it is suggested that it is a case of 'resilience without development'. It is likely that the findings of the study could have wider relevance among rural communities elsewhere in Africa.